Chemical Constituents and Coagulation Activity of Amygdalus persica L. Flowers. (20th May 2021) - Zhang, Juanjuan; Yin, Zhenhua; Chen, Lin; Yang, Baocheng; Zhang, Wei; Kang, Wenyi
Abstract : Amygdalus persica L., belongs to Rosaceae family, and its flowers are used as medicine and food. n -Butanol extract of A. persica flowers were isolated and purified with various column chromatographies, and the fourteen compounds, chlorogenic acid butyl ester (1 ), rutin (2 ), protocatechuic acid (3 ), caffeic acid (4 ), 5-O-coumarroylquinic acid methyl ester (5 ), kaempferol-3-O-neohesperidoside (6 ), quercetin-3-O- β -D-glucoside (7 ), 3, 5-dicaffeoylquinic acid (8 ), quercetin-3-O- α -L-rhamnoside (9 ), 5-O-coumaroylquinic acid (10 ), kaempferol-3-O- α -L-rhamnoside (11 ), kaempferol-3-O- β -D-galactoside (12 ), D-glucitol (13 ), and multiflorin A (14 ), were identified by spectroscopic data and physical data. All the compounds except compound 2 were identified from A. persica flowers for the first time. The compounds were investigated for their coagulation activity by activated partial thromboplastin time (APTT), prothrombin time (PT), thrombin time (TT), and bibrinogen (FIB) in vitro . The results of coagulation activity showed that rutin (2 ), caffeic acid (4 ), kaempferol-3-O-neohesperidoside (6 ), kaempferol-3-O- α -L-rhamnoside (11 ), and kaempferol-3-O- β -D-galactoside (12 ) exhibited significant procoagulant activity, while chlorogenic acid butyl ester (1 ) possessed anticoagulant activity in vitro .